A Study on The Positive and Negative Impacts of Online Learning at The Graduate Level (Proceedings of the International Conference on Future of Education, 2022)
Now a day’s online learning has been adopted rapidly by educational institutions. Online learning has become an important part of the education agenda around the world. This study examined the impacts and effectiveness of online learning at the graduate level. The objective of the research was to explore the online learning system at the graduate level and find out the positive and negative impacts of the online learning system. The descriptive mixed method was used. The sample was MA students of six departments from the faculty of social sciences. The population was the female campus of International Islamic University and the total population was 445 students and the sample size was 210. A standardized questionnaire was used (close &open-ended questionnaire). For data analysis, the mean was used. The results indicated online learning is learning something through the internet. students face challenges in online learning like internet issues, electricity issues, distracting environment, technical issues, and lack of resources. Positive impacts were: online learning develops technical and digital skills among students, students can learn easily, it is flexible, and it increases students’ attendance in online classes. The negative impacts are that online learning needs more time, and effort for learning, lack of student participation, and less interaction between students and teachers. This study is helpful for the educational sector in improving the quality of online learning. It is recommended to HEC and the university to provide resources and advanced devices for the students to work or at least ensure that any online learning activities can be completed with a smartphone because through this all students can get benefit from online learning.
Keywords: positive; negative; online learning; impact; university level; methodology